2010
DOI: 10.1042/bj20100096
|View full text |Cite
|
Sign up to set email alerts
|

Adaptor protein 2 regulates receptor-mediated endocytosis and cyst formation inGiardia lamblia

Abstract: Synopsis The parasite Giardia lamblia possesses peripheral vacuoles (PVs) that function as both endosomes and lysosomes and are implicated in the adaptation, differentiation, and survival of the parasite in different environments. The mechanisms by which Giardia traffics essential proteins to these organelles and regulates their secretion have important implications in the control of parasite dissemination. In this study, we describe the participation of the heterotetrameric clathrin-adaptor protein gAP2 compl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
95
0

Year Published

2011
2011
2024
2024

Publication Types

Select...
4
3

Relationship

1
6

Authors

Journals

citations
Cited by 42 publications
(99 citation statements)
references
References 51 publications
4
95
0
Order By: Relevance
“…In Giardia, low-density lipoprotein (LDL) is taken up via a clathrin-dependent pathway (35,36). As with giActin, inhibition of the Giardia clathrin-mediated endocytosis pathway does not prevent the uptake of fluid-phase markers (36). We analyzed the ability of actin knockdown cells to endocytose fluorescent Bodipy-LDL.…”
Section: Resultsmentioning
confidence: 99%
“…In Giardia, low-density lipoprotein (LDL) is taken up via a clathrin-dependent pathway (35,36). As with giActin, inhibition of the Giardia clathrin-mediated endocytosis pathway does not prevent the uptake of fluid-phase markers (36). We analyzed the ability of actin knockdown cells to endocytose fluorescent Bodipy-LDL.…”
Section: Resultsmentioning
confidence: 99%
“…Several groups have presented evidence for a role of clathrin in endocytosis in Giardia (Touz et al, 2004;Hernandez et al, 2007;Gaechter et al, 2008;Rivero et al, 2010). However, neither typical membrane-associated clathrin lattices nor emerging clathrin-coated pits have been observed in this parasite.…”
Section: Clathrinmentioning
confidence: 99%
“…However, a recent work showed, by immunofluorescence and 3-D reconstruction, that the ER membranes are found throughout the cytoplasm, but do not permeate the space occupied by PVs (Faso and Hehl, 2011). Recently, it was shown that a mechanism of receptor-mediated endocytosis occurs in this organism, with specific molecules selectively directed to the PVs through a classical endocytic mechanism (Rivero et al, 2010;. These data suggest that uptake of soluble material into PVs is not selective at this step but is still capable of redirecting specific molecules to the TVN (Hernandez et al, 2007;Abodeely et al, 2009b).…”
Section: The Endosomal/lysosomal System Of Giardiamentioning
confidence: 99%
See 2 more Smart Citations